Pengaruh Perbedaan Penerapan Model Contextual Teaching And Learning Dan Model Think Pair Share Terhadap Hasil Belajar Perawatan PC - Atan Pramana (IAI Darussalam, 2016)
This study was conducted with the aim to see the effect of different application of learning model ncontextual teaching and learning and model of thinking pair share to PC PC learning outcomes. This research is an experimental research using quasi experiment plan (quasi experiment). The population of this study is all students of class X SMK Negeri 3 Malang academic year 2010/2011. The data analysis technique used a SPSS-t-assisted t-test used to reveal differences in learning outcomes due to the application of two different models. Based on the results of research from data analysis conducted, resulting in conclusion there is an increase in student learning outcomes before being treated and after being treated. The t-test results revealed that there was a significant difference in mean PC PC learning outcomes between the groups taught using the contextual teaching and learning learning model and the groups taught using the think pair share learning model